Foodborne pathogens : hazards, risk analysis, and control - Blackburn, Clive de W.; McClure, Peter J. (CRC Press ; Woodhead, 2002)
As trends in foodborne disease continue to rise, the effective identification and control of pathogens becomes ever more important for the food industry. With its distinguished international team of contributors, Foodborne pathogens provides an authoritative and practical guide to effective control measures and how they can be applied in practice to individual pathogens.
Keywords: Foodborne diseases.; Food -- Microbiology.; Risk assessment.; elektronické knihy; electronic books